コロニー デノ アデリー ペンギン ノ カウント キセツ ヘンカ ト ネン ヘンカ - 綿貫, 豊; ワタヌキ, ユタカ; 内藤, 靖彦; ナイトウ, ヤスヒコ; Watanuki, Yutaka; Naito, Yasuhiko (1992)
P(論文) 昭和基地周辺において, アデリーペンギン(Pygoscelis adeliae)繁殖コロニーの成鳥個体数は季節的に変化する。成鳥は10月20日から25日にコロニーに戻り始めた。成鳥数は11月10-20日に最大数に達し, その後減少し, 12月1-10日には比較的安定した。この季節的変化パターンはいずれの年, コロニーにおいても変わらなかった。信頼できる繁殖個体数を推定するために11月中旬と12月上旬にセンサスを行うのがよいだろう。 The number of Adelie penguin (Pygoscelis adeliae) adults at colonies around Syowa Station changes seasonally. The penguins started to arrive at the colonies on 20-25 October. The number of adults at each colony reached its maximum on 10-20 November, decreased until late November and was stable on 1-10 December. This seasonal pattern was consistent over years and colonies. Censuses in mid-November and early December are recommended since they could give reliable numbers of breeding pairs. departmental bulletin paper